Kesiapan BUM Desa Kabupaten Pandeglang untuk Mengimplementasikan Panduan Pelaporan Keuangan BUM Desa (Studi Kasus di 4 Klasifikasi BUM Desa) - Kodirin, Kodirin; Hamzah, Andy Prasetiawan; Setiya, Tanda; Muhaemin, Mochamad (Publikasi Penelitian Terapan dan Kebijakan, 2024)
ABSTRACT This research analyzes the readiness of Village Owned Enterprises (BUM Desa) Pandeglang Regency to Financial Reporting Guidelines for BUM Desa/Joint BUM Desa. The aim of this research is to compare the completeness and accuracy of the 2022 BUM Desa financial reports, compare the readiness of organizational commitment, human resources, supporting facilities, salaries/incentives, other aspects, and the BUM Desa strategy in implementing the Guidelines. This research is qualitative research with a descriptive approach. The research uses a case study method with locus of four Village BUMs with different classifications based on the BUM Desa Ranking. The research results show that all BUM Desa that are the focus of the research have not prepared 2022 financial reports. They just make a cash in and cash out report or a sales and expense report book. All BUM Desa that are the research locus do not have organizational commitment readiness, do not have human resources readiness, do not have supporting facilities readiness and do not have salary/incentive readiness. All Village BUMs that were the research focus mentioned training as another aspect that helps readiness. This is in line with the strategy for implementing the BUM Desa Financial Reporting Guidelines proposed by all BUM Desa that are the research locus, namely training in preparing financial reports according to the Guidelines. Some BUM Desa have added mentoring, documenting proof of transactions and providing supporting facilities as other strategies. Keywords: BUM Desa, Financial Reports, Guidelines, Pandeglang, Readiness